Antifungal activity of acidic electrolyzed water against strawberry postharvest molds (Fragaria x ananassa Duch cv. Camarosa) - Beatriz Elena Guerra Sierra; Adriana Sandoval; Liliana Torcoroma (Acta Agronómica)
The aim of this word was to assess the in vitro antifungal activity of acidic electrolyzed water (AEW) and the required contact time to inhibit the development of post-harvest molds common in strawberry fruit.  Ninety-four strawberry samples were used.  A five-fold assay in a randomized design was carried out using standard inoculum of fungal conidia, which were subjected to an array of contact times and AEW concentrations, using a controlled agitation (120 r.p.m) at 23°C.  The conidia treated with AEW were grown on potato dextrose agar and their germination was evaluated.  Mycelial growth of the treated samples was measured and compared against conidia control samples treated with distilled water instead of AEW.  Botrytis cinerea and Rhizopus stolonifer were the most commonly isolated species at 54.25% and 28.72%, respectively.  AEW inhibited conidia germination after 7 minutes of exposure.  The AEW concentration required to inhibit conidia germination was 10 ppm and 50 ppm for R. stolonifer and B. cinerea respectively, a variance possibly due to the constitution of their cellular walls.  A short exposure of AEW is able to inhibit post-harvest fungi growth, and is thus recommended as an efficient, economical, and environmentally sustainable sanitation agent, with the ability of extending the strawberry post-harvest consumption period.